Localization of the primary gustatory cortex within insular lobe using structural white matter connectivity evidence as determined by diffusion tensor imaging - Kamil, Wan Sarah Wan Ahmad (2022)
INTRODUCTION: The primary taste cortex localisation has been inconsistent in previous research. The current study aims to divide the insular lobe into subdivisions to determine investigate their individual structural connectivity to taste processing areas of the brain. MATERIALS AND METHODS: Diffusion-weighted imaging data from thirteen healthy female participants were obtained from a databse built in 2013. All participants had normal taste perception as determined by the modified Monell-Jefferson Taste & Smell Questionnaire. Probabilistic tractography using FMRIB Software Library (FSL) was performed to determine the relative connection probability of eleven divisions of insula lobes to target brain areas shown to be associated with taste processing, namely amygdala, frontal operculum and ventral striatum. RESULTS: The inferior part of the middle lobe and the inferio-posterior part of the anterior lobe of the insula had the highest connection probability to the areas of taste processing targeted in this research. The posterior lobe of the insula had the least connection probability to all targets as shown in previous research, while the frontal operculum had widespread connection to all lobes of the insula. The results of this research are with the statistical value of p<0.05. CONCLUSION: The inferior aspect of the middle lobe and the inferio-posterior part of the anterior lobe of the insula had the highest probabilistic connection to the areas of taste processing making it highly probable to be the site for primary taste cortex.